EVALUASI SISTEM PEMBINAAN SEKOLAH CATUR HARRY KURNIAWAN DI KABUPATEN SIDOARJO - SUTION, INDRA (Jurnal Prestasi Olahraga, 2013)
Chess is a mental game played by two people. In sports performance coaching chess scouting talented athletes is absolutely organized as early as possible. Scouting aims to get seeds gifted athlete as a successor to the outstanding athlete. Talented chess players likened the quality of raw materials to be processed into high-quality goods. To achieve the goal of becoming an athlete or an accomplished chess player is not easy, because it takes awareness, discipline, patience and perseverance. Achievement can not be achieved in a matter of weeks or months but years, through increased little by little from the regular practice. Sports coaching course in need of funds since establishing to support sports clubs are not little funding is needed. Therefore we need a strong source of funds from both the government and private sectors. Facilities and infrastructure are an important tool to facilitate in the achievement that affect the maximum performance improvement, on the other hand also want to make the school chess Harry Kurniawan as a talented athlete printer. The purpose of this study to know the coaching system, achievement, athlete training conditions, and how to recruit athletes in the school chess Harry Kurniawan Sidoarjo. Objectives of this research is the management, coaches, and athletes chess school Harry Kurniawan Sidoarjo. The method in this study used qualitative methods desikriptif, while the data collection is done using interviews. The results are 1) Harry Kurniawan coaching chess schools implementing guidance through a. Organizational management board which is not good, b. The process of regular exercise and a well-planned, c. Standards of quality coaches. Program performance coaching chess school athlete Harry Kurniawan implemented in stages. Planning and training program is based on the experience of the coach. 2) Achievement've gained Harry Kurniawan chess school athletes are very proud because athletes have won three National Championship. 3) Facilities and infrastructure owned by Harry Kurniawan chess school is very good and complete, including a gym, display boards, informator book, computer, folding boards, chess pieces, chess clock, rest rooms and a delivery vehicle matches athletes athletes condition is quite good. Keywords: Evaluation, Development, Chess.